2001
DOI: 10.1210/endo.142.10.8441
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of MAPKs in Y1 Mouse Adrenocortical Tumor Cells

Abstract: The regulation of the MAPKs, Erk(1) and Erk(2), and the MAPK kinase, Mek, were examined in the Y1 mouse adrenocortical tumor cell line and in the protein kinase A-defective mutant, Kin-8. ACTH and basic fibroblast growth factor each increased Mek phosphorylation and stimulated Mek activity in both cell lines and also activated the Erks at concentrations that paralleled their effects on Mek. The specific Mek inhibitor, PD98059, blocked the activation of the Erks by ACTH and basic fibroblast growth factor, indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 17 publications
4
21
0
Order By: Relevance
“…Because the ACTH-stimulated activation of mitogen-activated protein kinases (MAPKs) is largely independent of cAMP-dependent protein kinase (PKA) (26), we tested the ability of ACTH to stimulate the phosphorylation of the MAPKs extracellular signal–regulated kinases (ERKs) ERK1 and ERK2 in serum-deprived cells transfected with plasmids encoding MC2R and either MRAP or MRAP2 (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Because the ACTH-stimulated activation of mitogen-activated protein kinases (MAPKs) is largely independent of cAMP-dependent protein kinase (PKA) (26), we tested the ability of ACTH to stimulate the phosphorylation of the MAPKs extracellular signal–regulated kinases (ERKs) ERK1 and ERK2 in serum-deprived cells transfected with plasmids encoding MC2R and either MRAP or MRAP2 (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Srx expression is known to be regulated via two distinct transcriptional factors, AP-1 and nuclear factor erythroid 2-related factor (Nrf2). ACTH activates ERK via a cAMP-dependent pathway in Y-1 mouse adrenocortical tumor cells (Le & Schimmer, 2001), and ERK activation leads to AP-1 activation. We found that injection of ACTH increased the abundance of Srx in the adrenal glands of wild-type and Nrf2 knockout (KO) mice by similar extents, whereas induction of HO-1, whose gene is a well-characterized target of Nrf2, was apparent in wild-type mice but not in Nrf2 KO mice (Kil et al, 2012).…”
Section: Induction Of Srx By Acthmentioning
confidence: 99%
“…This leads to an increase in the expression of steroidogenic enzymes and steroidogenesis (1,2,17,18). In recent years, the data relating ERKs and steroidogenesis has been increasing steadily (3,11,(19)(20)(21). Even so, it cannot be discarded that this activation of ERKs 1/2 is also related to proliferation of adrenal cortex cells, since ACTH also increases the expression of Proliferating Cell Nuclear Antigen (PCNA) in the adrenal gland (22).…”
Section: Is Erks 1/2 Activation Exclusively Directed At Stimulation Omentioning
confidence: 99%
“…Upon binding it activates the cAMP/PKA -signaling cascade, leading to steroidogenesis (1,2). Recently, it has been described, namely in the Y1 adrenocortical tumor cell line, that ACTH could act via other cascades such as the Mitogen Activated Protein Kinase (MAPK) cascades (3,4).…”
Section: Introductionmentioning
confidence: 99%